Perilaku Metakognisi Siswa Dalam Menyelesaikan Masalah Kimia - Meylan Ratnawati; Nurdin Rahman; Siang Tandi Gonggo (Mitra Sains, 2015)
This study describes the metacognition behavior of students on problem solving in degree of acidity calculation. This research was conducted at SMAN 1 Pamona Utara and at SMA GKST 2 Pamona Puselemba. Research subjects were 6 students of class XII IPA determined based on the respondents test selection into high, middle and low categories. This study is a qualitative research. Research data were as test results, thinking-aloud transcripts, and interviews as well as the results of the inventory questionnaire metacognition activity. The data were described and tested using the triangulation method. Results of thinking-aloud data analysis showed that the high and the middle categories were able to assess the mistakes. The high category tend to monitor mistakes while making calculations. The middle category emphasized on parts of calculations to avoid mistakes and justify the calculations and the solutions. The middle category also tend to check the problem solving steps. The low category checked the answers. Results of the questionnaires showed that the average metacognition activity of the middle category was the highest, and the low category was the lowest. The lack of students' knowledge on the concepts and principles of the problem caused students could not solve the problem either. The highest level of students' metacognition in this study was the strategic use.